Ionic cross-linked chitosan beads for extended release of ciprofloxacin: In vitro characterization - Srinatha A.; Pandit J.; Singh S. (My University, 2025)
Chitosan beads loaded with ciprofloxacin hydrochloride were fabricated by ionic cross-linking with sodium tripolyphosphate. The beads showed an excellent water retention property. The degradation of fabricated beads was influenced by the pH of test medium. High drug load was achieved within the bead with a short curing time. Drug release was high in acidic medium (pH 1.2) vis-à-vis intestinal medium (pH 7.4). Ciprofloxacin hydrochloride release increased with an increasing concentration of ciprofloxacin and decreasing proportion of chitosan. Drug release followed both first-order and Higuchi's root time kinetics showing non-Fickian release mechanism.